Mean platelet volume and immature platelet fraction as predictors of early onset neonatal sepsis risk in neonates of 28-36 weeks gestational age - Indah Septiane; Fiva Aprilia Kadi; Tetty Yuniati; Nina Surtiretna; Aris Primadi (Paediatrica Indonesiana, 2022)
Background Early onset neonatal sepsis is a potential life-threatening problem for preterm infant. Diagnosing early onset neonatal sepsis is challenging. Difficulties in establishing diagnosis might cause delay definitive treatment. Objective To analyze for potential associations between early onset neonatal sepsis (EONS) risk and mean platelet volume (MPV) as well as immature platelet fraction (IPF) in neonates of 28-36 weeks gestational age. Methods A prospective cohort study was conducted at Dr. Hasan Sadikin General Hospital, Bandung, West Java. Mean platelet volume (MPV) and IPF were evaluated in the first ?6 hours of life and during the 48-72 hours after the first examination. This examination was followed by observation for sepsis development. Double logistic regression analysis was used. Results Of 115 subjects, 45 preterm infants (39.1%) developed early onset neonatal sepsis. The increase in both mean MPV and mean IPF were significantly different (P<0.05). Double logistic regression analysis revealed that an increase in mean MPV (ORadj=6.14; 95%CI 1.99 to 18.96; P=0.002) and mean IPF (ORadj=6.56; 95%CI 2.64 to 16.34; P<0.001) were significantly associated with increased risk of sepsis. Conclusion The MPV and IPF increase are associated with greater incidence of EONS in preterm infants.